Comparative Cost Efficiency Analysis of Smart Contracts: A Supply Chain Case Study on Polygon zkEVM - Pamungkas, Hedy (Riviera Publishing, 2025)
This paper presents the findings of research that addresses the primary economic barrier preventing blockchain adoption in supply chain management. While blockchain technology has the potential to deliver revolutionary benefits to supply chains, the non-viable nature of Ethereum's on-chain usage, with gas fees of 20.40 to 36.57 per transaction, represents a significant economic cost to enterprises, becoming an insurmountable obstacle, especially in emerging markets. The research employs a radical empiricism approach, systematically measuring the gas cost of over 300 independent test transactions for recording the flow of product materials, validating new vendors, and tracking distributed items against three modular smart contracts: a master contract and two interchangeable module contracts. The identical sets of contracts are deployed across the testing environment of the Polygon zkEVM mainnet, Polygon Cardona testnet, and Ethereum Sepolia testnet, with significance supported at p < 0.01 through a two-tailed t-test. The findings of the research demonstrated that the analyzed network, Polygon zkEVM, was able to demonstrate a 99.90% reduction of costs, from 143.25 to 0.14 for deployment costs and from 8.25 to 0.008 per transaction. The implementation options provide Polygon zkEVM with an extra 46.5% decrease in costs through the use of gas pricing as a determining factor in optimization, as well as an additional 90.9% decrease in costs through operational optimization, as the assessed costs remain less than 0.10% of the generated revenue, meeting the defined economic viability threshold for a need to process 500 transactions daily by an SME in Indonesia.